Georgia : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2003)
This Report on the Observance of Standards and Codes (ROSC) provides a review of Georgia's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. Georgia has made good progress in improving its statistics in a number of areas. Nonetheless, substantial shortcomings are present in some statistical practices and databases. Some of these shortcomings could be addressed with current resources.